2019
DOI: 10.1111/bjd.18025
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and neurokinin 1 receptor are new targets for the treatment of chronic pruritus*

Abstract: Summary Background Chronic pruritus is a distressing symptom associated with various dermatological conditions and systemic diseases. Current treatment options are often inadequate, resulting in impaired quality of life for many patients. An understanding of the underlying mechanisms of itch across pruritic conditions is important for development of effective, targeted treatments for chronic pruritus. Objectives To provide an overview of the pathogenesis of chronic pruritus, focusing on the role of substance P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 77 publications
1
56
0
1
Order By: Relevance
“…EGFRI-induced pruritus arises acutely within the first 2 weeks after initiation of the anticancer therapy5 and cutaneous accumulation, and activation of dermal mast cells16 17 62 may be the most important driver of the itch signalling in these patients. This acute course contrasts with that of chronic pruritus conditions (defined as being >6 weeks in duration),63 which are now linked to the sensitisation of itch signalling pathways similar to chronic pain, such that patients may report spontaneous itch (alloknesis) or an enhanced itch to normal itch-evoking stimuli (hyperknesis) 32 64 65. NK1 antagonists have shown great promise in randomised, placebo-controlled clinical studies as treatments for chronic pruritus conditions in general66 67 as well as specifically for prurigo nodularis,68 atopic dermatitis-associated pruritus69 and psoriasis-associated pruritus 70.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFRI-induced pruritus arises acutely within the first 2 weeks after initiation of the anticancer therapy5 and cutaneous accumulation, and activation of dermal mast cells16 17 62 may be the most important driver of the itch signalling in these patients. This acute course contrasts with that of chronic pruritus conditions (defined as being >6 weeks in duration),63 which are now linked to the sensitisation of itch signalling pathways similar to chronic pain, such that patients may report spontaneous itch (alloknesis) or an enhanced itch to normal itch-evoking stimuli (hyperknesis) 32 64 65. NK1 antagonists have shown great promise in randomised, placebo-controlled clinical studies as treatments for chronic pruritus conditions in general66 67 as well as specifically for prurigo nodularis,68 atopic dermatitis-associated pruritus69 and psoriasis-associated pruritus 70.…”
Section: Discussionmentioning
confidence: 99%
“…Scratching behaviour induced by intradermal injection of either SP or an NK1 agonist or topical administration of a hapten in animals can all be profoundly reduced by NK1 antagonist treatment, including both orvepitant and aprepitant 27–30. These data suggest that the NK1 receptor system is involved in itch signalling and therefore blockade of these pathways with NK1 receptor antagonists represents a potentially promising therapy for pruritic conditions, including EGFRI-induced pruritus 31 32…”
Section: Introductionmentioning
confidence: 98%
“…SP exerts its function mainly, but not exclusively, through its receptor NK1R (Azimi et al, 2017;Ständer and Yosipovitch, 2019). SP stimulates NK1R expressing cells, resulting in the release of additional itch mediators and evoking itch (Yosipovitch et al, 2018).…”
Section: Cd68(d) Macrophages Express Nk1rmentioning
confidence: 99%
“…SP binds to NK-1R, as well as the Mas-related G protein-coupled receptor (Mrgpr). NK-1R is more substantiated in eliciting pruritic response in humans as it induces vasodilatation, degranulation of mast cells, nerve growth factor (NGF) expression in keratinocytes and stimulates neurogenic inflammation [51]. In the study by Nattkemper et al [52], the authors utilized RNA sequencing and observed increased levels of both SP and NK-1R in lesional skin of patients with psoriasis and AD who experienced severe pruritus.…”
Section: Neurokinin-1 Receptor Antagonistsmentioning
confidence: 99%